2020
DOI: 10.1002/adfm.201909092
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Multilevel‐Stable Remanence States in Exchange‐Biased System through Spin‐Orbit Torque

Abstract: Multilevel remanence states have potential applications in ultra-high-density storage and neuromorphic computing. Continuous tailoring of the multilevel remanence states by spin-orbit torque (SOT) is reported in perpendicularly magnetized Pt/Co/IrMn heterostructures. Double-biased hysteresis loops with only one remanence state can be tuned from the positively or negatively single-biased loops by SOT controlled sign of the exchange-bias field. The remanence states associated with the heights of the sub-loops ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 49 publications
2
38
1
Order By: Relevance
“…[ 18 ] Meanwhile, the nonvolatility of these 2 n magnetization configurations in a single cell could serve as a pivotal ingredient for realizing multifunction and reconfigurable logics‐in‐memory. [ 31–38 ] Such a versatile platform could thus be useful for in‐memory computing architecture for potentially breaking the von Neumann bottleneck and reducing energy cost and computation delay due to data shuffling. [ 5,39,40 ] These important facts motivate the present study.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Meanwhile, the nonvolatility of these 2 n magnetization configurations in a single cell could serve as a pivotal ingredient for realizing multifunction and reconfigurable logics‐in‐memory. [ 31–38 ] Such a versatile platform could thus be useful for in‐memory computing architecture for potentially breaking the von Neumann bottleneck and reducing energy cost and computation delay due to data shuffling. [ 5,39,40 ] These important facts motivate the present study.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Beyond today's binary storage, a new proposal is to use the multi-level cell (MLC) to store more than two bits. [5][6][7][8] In addition, the MLCs can also be employed in spin-neuron-like devices, which have a large potential to significantly increase their computational performances. [9,10] Recent studies reported different efforts toward the multi-level devices, such as spinorbit torque based devices, [5] antiferromagnetic-based devices, [6] resistive random access memories (ReRAMs), [7] and ferroelectric field-effect transistors (FeFET).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] In addition, the MLCs can also be employed in spin-neuron-like devices, which have a large potential to significantly increase their computational performances. [9,10] Recent studies reported different efforts toward the multi-level devices, such as spinorbit torque based devices, [5] antiferromagnetic-based devices, [6] resistive random access memories (ReRAMs), [7] and ferroelectric field-effect transistors (FeFET). [8] However, a successful design transferable to the industrial processes has not been One of the critical issues in spintronics-based technologies is to increase the data storage density.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the STT effect, the magnetization reorientation can be also induced by spin‐orbit torque (SOT). As shown in Figure 1c, [ 41 ] the SOT effect in a multilayer of heavy metal (HM), FM, and antiferromagnetic (AFM), which may consist of various other magnetic combinations, originates from a spin‐orbit interaction, such as the spin Hall effect (SHE). [ 75 ] When an in‐plane current flows through the HM layer with a collinear magnetic field, the electrons with antiparallel spins experience spin‐scattering to its interface while going through this layer, leading to spin accumulation at the interface.…”
Section: Memristors and Cbasmentioning
confidence: 99%